A LONGITUDINAL INVESTIGATION OF EXPLICIT AND IMPLICIT AUDITORY PROCESSING IN L2 SEGMENTAL AND SUPRASEGMENTAL ACQUISITION. Issue 3 (19th July 2021) - Sun, Hui; Saito, Kazuya; Tierney, Adam
Abstract: Precise auditory perception at a subcortical level (neural representation and encoding of sound) has been suggested as a form of implicit L2 aptitude in naturalistic settings. Emerging evidence suggests that such implicit aptitude explains some variance in L2 speech perception and production among adult learners with different first language backgrounds and immersion experience. By examining 46 Chinese learners of English, the current study longitudinally investigated the extent to which explicit and implicit auditory processing ability could predict L2 segmental and prosody acquisition over a 5-month early immersion. According to the results, participants' L2 gains were associated with more explicit and integrative auditory processing ability (remembering and reproducing music sequences), while the role of implicit, preconscious perception appeared to be negligible at the initial stage of postpubertal L2 speech learning.